READING INTEREST IN COLLEGE STUDENTS - Pamungkas, Nugroho Widhi Sunu (Journal of Education, Linguistics, Literature and Language Teaching, 2025)
All students in Indonesia have studied sequentially from the elementary school level, followed by the junior high school level and continued to the high school level and up to the undergraduate level. Of the many stages that students go through up to the undergraduate level, one of the many activities carried out during the learning stage is reading. Reading is a crucial stage for students in the learning process, especially collecting data and searching for information. Taking this into account, reading activities are very important for students, but with the times, there are more and more distractions which make students' interest in reading decrease. Therefore, the author carried out this research to find out how students' reading interest at Adibuana University is. This research uses quantitative research methods where the author uses surveys to collect data from 10 samples taken at Adi Buana University English Education study program for the 2021/2022 academic year and the data is processed using SPSS version 19. By carrying out this research the author hopes to get information about reading interest at Bachelor 1 stage at Adibuana University. The results obtained were that students had a relatively high interest in reading as evidenced by the number of frequent answers input by the subjects during the data collection process